GRAMMAR INSTRUCTION IN TEXTBOOKS: A COMPARATIVE ANALYSIS OF ACCESSIBILITY FOR VISUALLY IMPAIRED STUDENTS (Web of Teachers: Inderscience Research, 2024)
This article explores the challenges and strategies involved in teaching grammar to visually impaired students. It examines relevant theories of language acquisition, including Universal Grammar, the Input Hypothesis, and Vygotsky's sociocultural theory, and discusses the unique needs of visually impaired learners within the context of special education. The article emphasizes the importance of multisensory approaches, assistive technologies, and inclusive instructional practices in facilitating grammar learning for this population. Key strategies discussed include the use of tactile materials, auditory aids, and technology-enhanced learning environments. The article concludes with recommendations for educators and researchers to further enhance grammar instruction for visually impaired students and promote their successful language development.